Acaricides Resistance in Ticks: Selection, Diagnosis, Mechanisms, and Mitigation - Obaid, Muhammad Kashif; Islam, Nabila; Alouffi, Abdulaziz; Khan, Alam Zeb; da Silva Vaz, Itabajara; Tanaka, Tetsuya; Ali, Abid (Frontiers in Cellular and Infection Microbiology, 2022)
Ticks are blood-feeding ecto-parasites that have a cosmopolitan distribution in tropical and subtropical regions of the world. Ticks cause economic losses in the form of reduced blood, meat and dairy products, as well as pathogen transmission. Different acaricides such as organochlorines, organophosphates, formamidines (e.g. amitraz), synthetic pyrethroids, macrocyclic lactones, fipronil, and fluazuron are currently used sequentially or simultaneously to control tick infestations. Most acaricide treatments now face increasingly high chances of failure, due to the resistance selection in different tick populations against these drugs. Acaricide resistance in ticks can be developed in different ways, including amino acid substitutions that result in morphological changes in the acaricide target, metabolic detoxification, and reduced acaricide entry through the outer layer of the tick body. The current literature brings a plethora of information regarding the use of different acaricides for tick control, resistance selection, analysis of mutations in target sites, and resistance mitigation. Alternatives such as synergistic use of different acaricides, plant-derived phytochemicals, fungi as biological control agents, and anti-tick vaccines have been recommended to avoid and mitigate acaricide resistance. The purpose of this review was to summarize and discuss different acaricides applied for tick control, their mechanisms of action and resistance selection, genetic polymorphisms in their target molecules, as well as the approaches used for diagnosis and mitigation of acaricide resistance, specifically in Rhipicephalus microplus ticks.